(untitled) (American Journal of Islam and Society, 2011)
The Pakistani scholar Fazlur Rahman disagreed with the German philosopher Hans-Georg Gadamer on elements of philosophical hermeneutics as they bear upon interpretation of texts ‒ in this case, the interpretation of the Qur’ān. Rahman proposed a “double-movement” theory of Qur’ānic interpretation through which he hoped for the revival and reform of Islamic intellectualism in its encounter with Western modernity, but also with difference from Islamic orthodoxy’s conceptualization of ijtihād. In this paper, I examine Rahman’s concerns as they relate to Gadamer’s general approach to understanding history and textual interpretation. Rahman argued that if Gadamer’s thesis concerning the forestructure1 of human understanding is correct, then Rahman’s theory has no meaning at all. I conclude that there is reason to see Rahman’s theory as consistent with Gadamer’s philosophical hermeneutics, albeit with some modification given Rahman’s focus on psychologism and objectivity as part of his approach to Qur’ānic interpretation. It is the tyranny of hidden prejudices that makes us deaf to what speaks to us in tradition. Hans-Georg Gadamer, Truth and Method